Mechanism of the Ketogenic Diet - J Gordon Millichap (Pediatric Neurology Briefs)
To elucidate the possible significance of ketone bodies in the mechanism of the ketogenic diet, researchers at Washington University School of Medicine, St Louis, MO, examined the effect of B-hydroxybutyrate and acetoacetate on excitatory and inhibitory synaptic transmission and spontaneous seizures in rat hippocampal slices and cultured hippocampal neurons.